DINAMIKA PERUBAHAN KEMASAN SIGARET KRETEK DI INDONESIA SEBAGAI WUJUD WARISAN BUDAYA - Dewi Isma Aryani; Kristianus Satrio Budi Nugroho (Jurnal Bahasa Rupa, 2021)
The development of cloves cigarettes and their packaging can be called a manifestation of physical culture according to Koentjaraningrat's description that an object is a physical product and the activities, deeds, and works of all humans are concrete. In addition, the development of the type of cloves cigarettes and their packaging fulfills the requirements for the stipulation of an object/intangible as a cultural heritage in accordance with Law Number 11 Year 2010 Chapter III Article 5. Therefore, the author attempts to explain the common thread from the history of Haji Djamhari's pioneering cloves cigarettes to changes in Indonesia’s cigarettes packaging when it began to be marketed in a modern way by Nitisemito to its effect on packaging designs that exist and circulate in society today. Less recorded fact that the cigarettes industry existed and developed in 1870-1880 in Kudus, the historical development of cloves cigarettes and its packaging in Indonesia at that time, cigarettes industry declining due to the racial riots in 1918, and the emergence of the subscription system also influenced the philosophy of creating cigarette packaging in Indonesia. The method used is descriptive qualitative with the theory of design, packaging, and branding so that the changes in cigarette packaging that occur in Indonesia are caused by the influence of market leaders from each type that exists, the image element is no longer the main logo but is replaced by logotype and logofont elements on packaging.